1998
DOI: 10.2466/pms.1998.87.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Body Perceptions of Bulimic and Nonbulimic Groups

Abstract: A brief survey measuring satisfaction with the body, concern for physical appearance, and motivations for selection of clothing was administered to 30 women in a university-sponsored support group for bulimic students and 30 women randomly selected from a college campus. No mean differences were found between the groups on concern for physical appearance when in a social setting, but mean differences were significant on satisfaction with weight, satisfaction with body image, and concern for physical appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Where clothing is often said to be used as camouflage for body-dissatisfied women (Rudd and Lennon, 2000; Frith and Gleeson, 2004) or to accentuate physical features of those who are satisfied with aspects of their bodies (Harden et al , 1998), a link between male clothing choice and self-image also seems logical. However, while prior research has examined modification of male self-image through exercise, or, at the extreme, plastic surgery (Pope et al , 2000; Gill et al , 2005), few studies explore the role of fashion consumption as a male self-image improvement tool.…”
Section: Literaturementioning
confidence: 99%
“…Where clothing is often said to be used as camouflage for body-dissatisfied women (Rudd and Lennon, 2000; Frith and Gleeson, 2004) or to accentuate physical features of those who are satisfied with aspects of their bodies (Harden et al , 1998), a link between male clothing choice and self-image also seems logical. However, while prior research has examined modification of male self-image through exercise, or, at the extreme, plastic surgery (Pope et al , 2000; Gill et al , 2005), few studies explore the role of fashion consumption as a male self-image improvement tool.…”
Section: Literaturementioning
confidence: 99%
“…In general, women who were dissatisfied with their bodies or with certain parts of their bodies have used clothing to conceal, minimize, or deemphasize those body parts. Harden, Butler, and Scheetz (1998) found that women who were less satisfied with their bodies often chose clothing to conceal the body, whereas those who were more satisfied chose clothing to accentuate the body. In Ogle’s (1999) study, participants used colors, fabrics, and styles to minimize certain areas of the body, such as by wearing black to appear thinner or choosing dresses and skirts that did not emphasize the hips.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Psychology research on body image and clothing behaviour depict clothing practices as one of the signifiers that predicts body-image disturbances and furthermore, evidence suggests that clothing practices can be used as a behavioural avoidance strategy to detract attention from body image and eating disorders (Trautmann et. al., 2007) or to conceal certain aspects of the body (Harden, Butler & Scheetz, 1998). The psychology literature has also linked fashion to narcissism (Larrain & Arrieta, 2007), eating disorders (Trautmann, Worthy & Lokken, 2007), over-dependence on others' approval (Freeburg & Workman, 2016), and loss of autonomy (Hardy, Merckelbach, Nijman & Zwets, 2007).…”
Section: Presentation and Structure Of Researchmentioning
confidence: 99%